Penyuluhan Keutamaan “Berbagi Sedekah” di Bulan Ramadhan - Lestari, Dirga Ayu; Syukri, Mahmud; Aisyah, Siti (STAI Publisistik Thawalib Jakarta, 2024)
Giving alms is an obligation for all those who are able, directed towards those in need. This community service was conducted to provide a strong understanding to the community about the importance of sharing and to assist those who are economically disadvantaged. The service activity was carried out using a Participatory Action Research (PAR) approach. The results of the service included the lecturers delivering material to the community about the importance of alms, the forms of alms, the benefits of giving alms and concluding with the distribution of gifts to the community by the lecturers and students. Conclusion: This community service activity was successfully conducted and had a positive impact on the community, both in terms of their knowledge and their economic situation.